Experimental analysis and machine learning modeling of optical properties of lithium disilicate glass–ceramics comprising lithium tantalate as a secondary phase. (24th March 2022) - DeCeanne, Anthony V.; Wilkinson, Collin J.; Dittmer, Marc; Ritzberger, Christian; Rampf, Markus; Mauro, John C.
Abstract: Color is an important property of lithium disilicate (LD) glass–ceramics for a variety of applications. For example, the color of dental glass–ceramics needs to be tuned to match the color of natural teeth. The present study examines the optical properties of LD glass–ceramics containing lithium tantalate as a secondary phase via ultraviolet–visible spectroscopy. A large data set is analyzed to investigate the relationship between heat treatments and optical properties, specifically the L * a * b * color coordinates. The color coordinates are dependent on the heat treatment following previously acquired phase data. The data are used to train a two‐step machine learning model to predict what heat treatment is needed to obtain a given set of color coordinates.